2007
DOI: 10.5897/ajb2007.000-2451
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological studies and antimicrobial properties of some Iron(III) complexes of Ciprofloxacin

Abstract: Two iron(III) complexes of Ciprofloxacin were synthesized by reaction of the ligand with iron(III) chloride hexahydrate in different solutions. The nature of bonding of the ligands and the structure of the isolated metal complexes were elucidated on the basis of their physical and spectroscopic studies. The infrared spectra suggest that two classes of compounds were obtained: molecular complex in which the ligands were bidentately bonded to the metal through the ring carbonyl oxygen and one of the oxygen of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…This agrees with the findings of (Hudson (1944); Kalu et al (1988); Adah et al (1992); Ismaila et al (2000); Umar et al (2008), which reported increase in serum liver enzymes level in experimental trypanosomiasis. Increases in the level of these enzymes are indications of damage to liver, brain, and cardiac muscles as documented by Kaplan et al (1988); Malomo (2000); Yakubu et al (2006); Obaleye et al (2007); Wurochekke et al (2008). Similarly, several workers have reported hepatocellular damage and generalized degenerative changes in other tissues and organs in trypanosomiasis (Anosa and Kaneko, 1984a,b,;Bruijn et al, 1987;Pentreath and Kennedy, 2004).…”
Section: Discussionmentioning
confidence: 86%
“…This agrees with the findings of (Hudson (1944); Kalu et al (1988); Adah et al (1992); Ismaila et al (2000); Umar et al (2008), which reported increase in serum liver enzymes level in experimental trypanosomiasis. Increases in the level of these enzymes are indications of damage to liver, brain, and cardiac muscles as documented by Kaplan et al (1988); Malomo (2000); Yakubu et al (2006); Obaleye et al (2007); Wurochekke et al (2008). Similarly, several workers have reported hepatocellular damage and generalized degenerative changes in other tissues and organs in trypanosomiasis (Anosa and Kaneko, 1984a,b,;Bruijn et al, 1987;Pentreath and Kennedy, 2004).…”
Section: Discussionmentioning
confidence: 86%
“…Similar increases in body weight, average daily gain and feed efficacy between the piglets of antibiotic positive control and EUF treatment were obtained in our present study. In addition, serum TP level and ALP activity could reflect the body protein metabolic stasis [26] and the alteration of soft tissue membrane permeability [27,28], respectively. Although these parameters' values were in physiological ranges, EUF supplementation promoted serum TP content and ALP activity compared to antibiotic positive control, which in a certain extent showing the increased nutrient efficiency and development of piglets and their organs [29].…”
Section: Discussionmentioning
confidence: 99%
“…The spread of infectious diseases is not just associated with poverty but also serve as major hindrance to economic development (Leonard, 1986;Ajibade, 2008). The current challenge faced by synthetic inorganic chemists is how to combat the resistance posed by pathogens to all classes of antimalarial drugs (Peter and Zijian, 1998;Obaleye et al, 2007;Rajee et al, 2018;Chu et al, 1996). Malaria is a major threat to health especially in Africa (Kannan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%